Samsung Galaxy Tabs for dummies - Gookin, Dan. (Laura Ann); 1906-1998.; 1970- (Hoboken, NJ John Wiley & Sons, 2014)
Blast into the Samsung Galaxy and experience your tablet in a whole new way. Gookin helps you get the most out of your Galaxy Note or Galaxy Tab and all its amazing features |c Sources other than Library of Congress.
Includes index. "Covers all Samsung Galaxy Tabs and the Galaxy Note!"--Cover.
Keywords: Samsung Galaxy Tab (Computer); Smartphones; Mobile computing; Computer